Myth of Wa Sirikamba in The Muna Community in Wali Village, Watopute District, Muna Regency - Muhammad, Sadam; Nurtikawati, Nurtikawati (Sean Institute, 2025)
This study aims to identify the forms and functions of the Wa Sirikamba myth in the life of the Muna community in Wali Village, Watopute District, Muna Regency, as well as to analyse the influence of this myth on their mindset and social behaviour. Employing a qualitative approach with ethnographic methods, data were collected through observations, in-depth interviews with local cultural figures and community members, as well as relevant documentary studies. Data analysis was conducted using Bronislaw Malinowski's functional theory, which emphasises the role of myths in maintaining social and cultural stability within communities. The findings indicate that the Wa Sirikamba myth is not merely an oral narrative but also involves sacred sites and belief rituals that bind the community in religious and social practices. This myth serves several important functions: (1) a social function as a tool for social control that shapes interactions among individuals, (2) a religious and spiritual function that connects the community with supernatural forces, (3) an ecological function that regulates the relationship between humans and nature, (4) an educational and moral function that instils local wisdom values, and (5) a mystical and magical function in spiritual life. This research asserts that the Wa Sirikamba myth is more than just a traditional story; it is an integral part of the belief system and cultural identity of the Muna community, remaining relevant within a modern social context.